A Scoping Review of the Evidence for the Medicinal Use of Natural Honey in Animals - Vogt, Nadine A.; Vriezen, Ellen; Nwosu, Andrea; Sargeant, Jan M. (Frontiers in Veterinary Science, 2021)
Honey has a history of medicinal use that predates written records. In recent decades, there has been renewed interest in the use of honey in human medicine, particularly for the treatment of burns and other wounds. Several recent systematic reviews in the human literature have demonstrated the efficacy of honey in the treatment of a number of conditions, including burns, wounds, and oral mucositis. The goal of this scoping review was to describe the nature and extent of the current body of evidence addressing the medicinal use of natural honey and/or its derivatives in animals. Although the focus of this review was the veterinary literature, all animal species except insects and humans were eligible, including animals used for biomedical research. Electronic databases searched were MEDLINE, CAB Abstracts, AGRICOLA, Web of Science Core Collection and Web of Science SciELO Citation Index. A total of 397 articles reporting 436 studies were included in this review. The majority of articles were biomedical research articles (n=350); fewer veterinary research articles were identified (n=47). Apart from one systematic review, all biomedical studies were challenge trials. Most veterinary studies were case reports/series (n=23), followed by challenge trials (n=18) and controlled trials (n=8). The animal species examined within veterinary articles consisted primarily of dogs, horses, cats and cattle, whereas the majority of biomedical research articles examined rats and mice. Wound healing was the most common indication examined; other indications examined included the prevention or treatment of gastric ulcers, bacterial and parasitic infections, toxic exposures, metabolic conditions (e.g., diabetes), and neoplasia. The majority of interventions consisted of non-medical grade honey (n=412/436), followed by medical-grade honey (n=29/436), and derivatives of natural honey (n=9/436). With much of the current veterinary literature consisting of case reports and case series, high quality primary veterinary research in the form of controlled trials or challenge trials is needed to advance this field, as well as to provide sound data for evidence-based assessments of the efficacy of honey in clinical veterinary practice.